2013
DOI: 10.1186/1745-6215-14-379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega-3 polyunsaturated fatty acid supplementation in patients with chronic chagasic cardiomyopathy: study protocol for a randomized controlled trial

Abstract: BackgroundChronic chagasic cardiomyopathy is an inflammatory disease that occurs in approximately 30% of patients infected by the protozoan Trypanosoma cruzi, and it has a profile of high morbidity and mortality. The worst prognosis and the progression of this cardiomyopathy are associated with an exacerbated immune response and the production of proinflammatory cytokines, which also occur in other cardiomyopathies. Some nutrients, including omega-3 polyunsaturated fatty acids (PUFAs), promote the inhibition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Recently, a group of Brazilian researchers reported that patients aging >18 years, with a diagnosis of CCC, that received LC n-3 PUFAs capsules (1.8 g EPA and 1.2 g DHA) during an 8-week period, presented modifications in the lipid and inflammatory profile, demonstrated by a decrease in triglycerides and improvements on IL-10 concentration [36]. The same group had already supposed in 2013 that the anti-inflammatory action of LC n-3 PUFAs may have beneficial effects on chronic chagasic cardiomyopathy, and could be translate into a less severe progression of cardiomyopathy, with subsequent reduction in morbidity [37].…”
Section: Long Chain N-3 Pufas and Trypanosoma Cruzi Infectionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, a group of Brazilian researchers reported that patients aging >18 years, with a diagnosis of CCC, that received LC n-3 PUFAs capsules (1.8 g EPA and 1.2 g DHA) during an 8-week period, presented modifications in the lipid and inflammatory profile, demonstrated by a decrease in triglycerides and improvements on IL-10 concentration [36]. The same group had already supposed in 2013 that the anti-inflammatory action of LC n-3 PUFAs may have beneficial effects on chronic chagasic cardiomyopathy, and could be translate into a less severe progression of cardiomyopathy, with subsequent reduction in morbidity [37].…”
Section: Long Chain N-3 Pufas and Trypanosoma Cruzi Infectionmentioning
confidence: 94%
“…6-Effects of in vivo supplementation of experimental mice during acute T. cruzi infection [22]. 7-Effects of in vivo supplementation of human patients with chronic Chagas cardiomyopathy [37]. Original publication [22].…”
Section: Long Chain N-3 Pufas and Trypanosoma Cruzi Infectionmentioning
confidence: 99%
“…The present study was a single-center double-blind clinical trial conducted at the Evandro Chagas National Institute of Infectious Disease (Rio de Janeiro, Brazil). The full description of the study protocol have been published previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that omega-3 PUFAs play beneficial effects on human health, including in neurodevelopment ( 1 ), eye function ( 2 ), and liver lipid metabolism ( 3 ). Omega-3 PUFA supplements are used in the treatment or prevention of diseases, such as depression, cardiovascular diseases ( 5 ), and inflammatory bowel disease (IBD) ( 6 ). The beneficial effects of omega-3 PUFAs on human health require adequate doses and duration, as a low dose of omega-3 PUFAs (180 mg of EPA and 120 mg of DHA) for 8 weeks does not have significant effects on inflammatory and oxidative stress markers in people with type 2 diabetes ( 7 ), while a higher dose of omega-3 PUFAs (1,200 mg DHA + EPA) for 12 weeks could improve insulin sensitivity and reduce the triglyceride levels in individuals with a high risk of type 2 diabetes ( 8 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%